Penerapan Algoritma Decision Tree C4.5 untuk Klasifikasi Kepribadian Peserta Didik di Yayasan Al-Mubarak - Irlanda, Dinda Claudia; Hariawan, Kurli; Rusdiah, Rudi (JATISI, 2025)
After the COVID-19 pandemic, the world of education has often been in the spotlight regarding the personality of each student, which means that the world of education in Indonesia is often considered to have failed in creating a young generation with noble morals, character and morals. There are many problems experienced by the world of education which cause moral values to decline, as well as cases of drug abuse, promiscuity, crime, bullying and various other acts of violence. A healthy school environment can create good personalities in students. Every problem recorded in the Guidance Counseling (BK) book is also varied, but the problems most often recorded are regarding the character and personality attitudes of students who are lacking. So the school, assisted by a psychology teacher, made a decision by conducting a personality test so that the lost character and attitudes of the students could grow again. The method used in this research uses a personality test with the C4.5 Algorithm method. The results of the method used will produce a personality classification from the test given to students who experience problems. So that Guidance Counseling Teachers can handle students based on the participants' personalities